The effects of the decentralization of collective bargaining on wage differences among employee groups - Kauhanen Antti (The Research Institute of the Finnish Economy (ETLA), 2024)
Recently, Finnish forest industries shifted from sectoral collective bargaining to firm-level bargaining, and the IT services industry shifted to a hybrid of sector- and firm-level bargaining. These changes meant that all issues previously covered by sectoral agreements would now be negotiated at the firm level, which could lead to notable contract changes. A study previously published by ETLA showed that decentralization of bargaining had only modest impacts on the level and dispersion of wages. Of the groups examined, only for blue-collar workers in paper industries, decentralization led to higher wages and increased wage dispersion within firms. This study examines the effects of the transition to firm-level agreements on pay differences between different groups. Previous international research has shown that decentralization of the collective bargaining system can lead to an increase in the gender pay gap or to an increase in the pay gap between different educational groups. The results of the study show that in Finland, the move away from union-specific bargaining did not increase pay differences between different groups.
Keywords: J31; J52; J53; 330; Firm-level bargaining; Earnings; Wage dispersion; Gender wage differences